(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Polycystic ovarian syndrome (PCOS) is one of the major health problems for women of reproductive age. In Pakistan, the prevalence of this syndrome is increasing with every passing year. Besides its rapid increase, the majority of Pakistani women do not have knowledge of this disease. The current study is intended to examine the experiences and challenges faced by women with PCOS. For this purpose, a sample of twelve women suffering from PCOS was interviewed through the purposive sampling technique. Eight out of twelve women were married, and four were unmarried. The researchers chose thematic analysis to analyze the data. The analysis revealed several major themes, including participants’ experiences with the diagnosis and awareness of PCOS, initial family reactions particularly from mothers and husbands—the impact of PCOS on mental and physical well-being, and common myths and misconceptions surrounding the condition. These findings indicate that there is an urgent need for raising awareness about PCOS among the public, particularly among young women. This study is significant as it sheds light on the personal and societal challenges associated with PCOS, highlighting the critical need for awareness and supportive interventions to improve the quality of life and well-being of affected women in Pakistan.